Analyzing the Width of the Maxillary Sinus from Private Practice in Bogor, Indonesia - Steven A. Tjang; Rosalina Tjandrawinata; Muhammad Novo Perwira Lubis (Faculty of Dentistry, Universitas Trisakti, 2018)
Background: X-ray examinations are still a frequent diagnostic tool used by doctors in Indonesia. However, there is an apparent lack of descriptive data regarding the size and location of the maxillary sinus in Indonesian people. Objective: The aim of this study is to provide descriptive data on the size and location of the maxillary sinus among patients in the city of Bogor, West Java, Indonesia. Methods: Sixty eligible subjects aged 17 to 70 years old were randomized into six groups: male and female patients between 17 and 25 years old; male and female patients between 26 and 45 years old; and male and female patients aged 46 or older. Radiographic pictures were taken using the X-mind Novus Digital Panoramic X-ray unit and data were measured using the software Digora for Windows. Results: Using an analysis of variance, we found that men have significantly larger maxillary sinus dimensions than women (79.05 mm compared to 66.33 mm). It also reveals that there are significant differences (p<0.05) between male and female groups; whereas 2 groups aged less than 46 years old are significantly different with group aged 46 years or older in both gender. Conclusion: The study demonstrates that the size and location of maxillary sinus differ significantly between men and women in Bogor and that they follow a specific trend.